Comparison of Treatment Outcomes of Intravenous versus Intra-arterial Chemotherapy in Retinoblastoma - Muhammad Usman; Fauzan, Ahmad; Arslan, Ahmed; Gul, Raheem (Indus Journal of Bioscience Research, 2025)
Background: Retinoblastoma is the most common intraocular malignancy in children. While systemic intravenous chemotherapy (IVC) has improved outcomes, responses remain suboptimal in advanced disease. Intra-arterial chemotherapy (IAC) offers targeted drug delivery, but direct comparative evidence remains limited in resource-constrained settings. Objective: To compare treatment outcomes of IVC versus IAC in patients with retinoblastoma. Methods: A quasi-experimental study was conducted at the Department of Ophthalmology, Lahore General Hospital, from July 2024 to June 2025. Ninety-two children with newly diagnosed intraocular retinoblastoma (stages B-E) were randomized into two groups of 46 patients each. Group A received systemic IVC with vincristine, etoposide, and carboplatin. Group B received IAC with melphalan, with topotecan or carboplatin added for resistant disease. Tumor response was assessed according to WHO Response Evaluation Criteria. Data were analyzed using chi-square test with significance at p<0.05. Results: Overall treatment efficacy was achieved in 34 patients (73.9%) in the IAC group compared to 23 patients (50.0%) in the IVC group (p=0.018). Complete remission was significantly higher in the IAC group at 39.1% versus 15.2% (p=0.024). Progressive disease occurred in only 4.3% of IAC-treated patients compared to 17.4% of IVC-treated patients (p=0.019). Disease control was achieved in 73.9% of IAC patients versus 50.0% of IVC patients. Conclusion: Intra-arterial chemotherapy demonstrated superior efficacy compared to intravenous chemotherapy in managing advanced retinoblastoma. These findings support adoption of IAC as a preferred treatment modality in suitable cases to maximize tumor control and eye preservation.